Parasitological diagnosis of Bovine Parasitic Sadness in Bahia - Retrospective study from 2017 to 2021 (Research, Society and Development, 2022)
The Bovine Parasite Sadness (BPS), caused by Babesia bovis and B. bigemina in combination with Anaplasma marginale, is responsible to cause injury to the national cattle farming. Scattered in all the regions of Brazil, it is estimated that the BPS caused an expenditure of about 3,5 million dollars for the national cattle farming in 2019. The objective of this paper was to accomplish a retrospective study comprising the years of 2017 to 2021 about the occurrence of these hemiparasites through cytological analysis of blood smears in cattle herds from 4 properties in the counties of Prado, Jucuruçu, São Sebastião do Passé and São Miguel das Matas, all located in the state of Bahia/Brazil. It was observed the presence of Babesia spp. in cattle farms located the counties of Prado (3,0%), Jucuruçu (7,4%) and São Sebastião do Passé (63,7%). It was equally observed in the latter a high occurrence of A. marginale (44,0%) with co-infection (89%). It has not been detected any of the hemiparasites that cause BPS in the farm located in São Miguel das Matas. This study shows the importance of cytological analysis of blood smears in the identification of these hemiparasites to support preventive measures by the state health agencies to avoid the exposure of animals to TPB agents.